Pedometers can help people get more active as part of an exercise programme. (6th April 2020) - Cook, Rob; Davidson, Peter; Martin, Rosie
The study: Hodkinson A, Kontopantelis E, Adeniji C, et al. Accelerometer- and pedometer-based physical activity interventions among adults with cardiometabolic conditions: a systematic review and meta-analysis . JAMA Network Open 2019;2:e1912895. This study was funded by the NIHR School for Primary Care Research (project number 390 ESWG Workstream 3). To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000880/pedometers-can-help-people-get-more-active-as-part-of-an-exercise-programme